Open House : 35 Historic Upstate New York Homes - D'Imperio, Chuck (Book collections on Project MUSE., 2020)
"Upstate New York author Chuck D'Imperio takes us behind the scenes of 35 homes throughout the region that are open to the public. Each house boasts of having a famous resident from the past. Whether it be a palatial mansion in the Hudson Valley, or a rustic cabin in the Adirondacks, each home has an interesting and important story to tell. This book is meant to act as a partner to the several other Upstate New York books D'Imperio has published through Syracuse University Press"--